Assessment of the level of physical fitness and development of college students - Sulaymanov Kurbonali; Yunusaliev Umarali (Genius Journals, 2023)
Nowadays, the improvement of physical education in the direction of health improvement in secondary special educational institutions depends on all-round objective and timely control and corrective measures.
Keywords: Indicators of physical training; training methods; physical development